Antiplatelet Therapy of Cilostazol or Sarpogrelate with Aspirin and Clopidogrel after Percutaneous Coronary Intervention: A Retrospective Cohort Study Using the Korean National Health Insurance Claim Database. - Yoojin Noh; Jimin Lee; Sooyoung Shin; Hong-Seok Lim; Soo Kyung Bae; Euichul Oh; Grace Juyun Kim; Ju Han Kim; Sukhyang Lee (PLoS ONE)
Background/objectives Addition of cilostazol or sarpogrelate to the standard dual antiplatelet therapy of aspirin and clopidogrel has been implemented in patients that underwent percutaneous coronary intervention (PCI) with stents in Korea. This study aimed to evaluate the efficacy and safety of triple antiplatelet therapies. Methods This retrospective cohort study was performed using the Korean National Insurance Claim Data of the Health Insurance Review and Assessment Service from January 1, 2009 to December 31, 2014. The study cohort population consisted of patients with ischemic heart diseases and a history of PCI. They were treated with antiplatelet therapy of aspirin, clopidogrel (AC); aspirin, clopidogrel, cilostazol (ACCi); or aspirin, clopidogrel, sarpogrelate (ACSa) during the index period from January 1, 2010 to December 31, 2011. During the follow-up period up to December 31, 2014, the major adverse cardiac or cerebral events (MACCE) including death, myocardial infarction, target lesion revascularization, and ischemic stroke were assessed. Bleeding complications were also evaluated as adverse drug events. Results Out of 93,876 patients with PCI during the index period, 69,491 patients started dual (AC) or triple therapy (ACSa or ACCi). The clinical outcomes of comparing ACSa and ACCi therapy showed beneficial effects in the ACSa group in the prevention of subsequent cardiac or cerebral events. After Propensity score-matching between ACSa and ACCi groups, there were significant differences in MI and revascularization, with corresponding HR of 0.38 (95% CI, 0.20-0.73) and 0.66 (95% CI, 0.53-0.82) in ACSa vs. ACCi at 12 months, respectively. At the 24-month follow-up, the triple therapy groups (ACS or ACC) had a higher incidence of MACCE compared to the dual therapy (AC) group; ACSa vs. AC HR of 1.69 (95% CI, 1.62-1.77); ACC vs. AC HR of 1.22 (95% CI, 1.06-1.41). There was no significant difference in severe or life-threatening bleeding risk among three groups; ACSa vs. AC, HR of 0.68 (95% CI, 0.37-1.24), ACCi vs. AC, HR of 0.91 (95% CI, 0.77-1.09). Conclusion Sarpogrelate-containing triple antiplatelet therapy demonstrated comparable rates of MACCE prevention to the conventional dual antiplatelet therapy after PCI without significantly increasing bleeding risk during the two-year follow-up period.